2021
DOI: 10.1037/ccp0000632
|View full text |Cite
|
Sign up to set email alerts
|

Treating trauma and aggression with narrative exposure therapy in former child and adult soldiers: A randomized controlled trial in Eastern DR Congo.

Abstract: Objective: Individuals who return from armed groups present with a history of traumatic events including perpetration. Subsequent severe mental stress and heightened levels of reactive and appetitive aggression may persist and if left untreated, frequently impede peacebuilding and societal stability. In this study, we tested a revised adaptation of Narrative Exposure Therapy (NET;Schauer et al., 2011) for Forensic Offender Rehabilitation (FORNET) implemented in a sample of male former combatants in war-torn re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 68 publications
2
20
0
5
Order By: Relevance
“…Thus, screening for traumatic events should become a routine part of psychological treatment. Combined trauma therapy with extended group sessions allowing for skills training and help to abstain from aggression has shown promising results ( Robjant et al, 2019 ; Koebach et al, 2021 ). In addition, systemic approaches help to de-escalate intrinsic family dynamics that lead to aggression and violence (e.g., Oka and Whiting, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, screening for traumatic events should become a routine part of psychological treatment. Combined trauma therapy with extended group sessions allowing for skills training and help to abstain from aggression has shown promising results ( Robjant et al, 2019 ; Koebach et al, 2021 ). In addition, systemic approaches help to de-escalate intrinsic family dynamics that lead to aggression and violence (e.g., Oka and Whiting, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aggression can be defined as any behavior intended to cause harm in others motivated either reactively, thus occurring as a response to a perceived threat, or instrumentally/proactively ( Anderson and Bushman, 2002 ). Increasing evidence points to the rewarding and thus self-perpetuating nature of aggression ( Nell, 2006 ; Elbert et al, 2010 , 2018 ; Koebach and Elbert, 2015 ; Golden and Shaham, 2018 ; Golden et al, 2019 ; Koebach et al, 2021 ). In recent aggression models, aggressive behavior is described as a consequence of situational (e.g., stress, frustration, discomfort, threatening stimuli) and personal factors (e.g., traits, attitudes, gender, trauma history), as well as internal states (e.g., cognition, affect, and arousal; e.g., Anderson and Bushman, 2002 ; Bushman, 2016 ; Elbert et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, a downward spiral seems to arise that accelerates the cycles of violence: Ex-combatants who live in a social environment that holds strong rejecting attitudes toward former recruits, who encounter social threats (which they often attribute to their armed group history), and who perceive this stigma doubt that reintegration and re-establishment of their social reputation are possible and in consequence likely feel lonely and dissatisfied with their "new" civilian life are likely less successful in minimizing trauma-and combat-related aggressive tendencies, which again decreases others' openness to reapproach and trust. paper Elbert et al, 2012;development Robjant et al, 2019;Koebach et al, 2021) as well as social tensions. Social approaches have shown promising results; however, they often either required intense individualized therapeutic guidance (e.g., multisystemic therapy, Limbos et al, 2007) or addressed general and not community-specific discriminatory attitudes and behavior toward particular groups (e.g., radio edutainment, Iqbal & Bilali, 2017).…”
Section: Understanding the Path To Mental Health Problems And The Continuation Of Violencementioning
confidence: 99%
“…Another strength of NET is that the majority of studies were conducted in humanitarian and emergency settings (e.g. Koebach, Carleial, Elbert, Schmitt, & Robjant, 2021 ; Neuner, Schauer, Klaschik, Karunakara, & Elbert, 2004 ; Orang et al, 2018 ; Schaal, Elbert, & Neuner, 2009 ). Biological studies have revealed impacts on the immune system (Morath, Gola, et al, 2014 ; Morath, Moreno-Villanueva, et al, 2014 ) and DNA methylation in genes relevant to memory processes (Carleial et al, 2021 ).…”
Section: The Netfacts Health System: Building Up On Evidence Based Trauma Therapymentioning
confidence: 99%